Efficacy of Pulsed Electromagnetic Field Therapy for Pain Management After Impacted Mandibular Third Molar Surgery. A Randomized Clinical Trial - Ferragina, Francesco; Caruso, Davide; Barca, Ida; Kallaverja, Elvis; Arrotta, Antonella; Cristofaro, Maria Giulia (Journal of oral and maxillofacial surgery, 2024)
Postoperative pain and swelling associated with the removal of the third molar (M3) adversely affect the patient’s quality of life. The study aims to measure pain reduction and analgesic use in patients treated with pulsed electromagnetic field (PEMF) therapy following M3 removal and compares it to patients who did not receive PEMF. The single-center study was designed as a randomized, prospective, controlled, double-blinded trial on a sample of patients with impacted mandibular M3 ascertained by x-ray orthopantomography and computed tomography. The predictor variable is postoperative pain management. It was assigned randomly to each subject who received either PEMF or standard therapy. The pain was quantified using a 100 mm visual analog scale and the number of analgesics taken. Each subject kept a daily clinical diary for 7 days, recording the amount of pain using the visual analog scale and the number of analgesic tablets taken. The study covariates were age, sex, tobacco use, and Pell and Gregory’s classification of M3s. Student’s t test was used, placing the statistical significance for P value < .05. The primary planned analysis was a 2-group, continuity-corrected, χ2 test of equality of proportions. The study sample included 90 patients, 47 men and 43 women, with an average age of 32.43 ± 8.80 years. PEMF was statistically associated with improved pain reduction (2.08 vs 5.04 with a P value = .0002) and consumption of fewer analgesics than the control group (2.6 vs 5.8 with a P value = .0062). The study’s results attest to the effectiveness of PEMF therapy in pain control after M3 surgery.